2004
DOI: 10.1016/s0378-1097(04)00002-3
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of response regulator gene,devR, leads to attenuation in virulence ofMycobacterium tuberculosis

Abstract: The devR-devS two-component system of Mycobacterium tuberculosis was identified earlier and partially characterized in our laboratory. A devR: :kan mutant of M. tuberculosis was constructed by allelic exchange. The devR mutant strain showed reduced cell-tocell adherence in comparison to the parental strain in laboratory culture media. This phenotype was reversed on complementation with a wild-type copy of devR. The devR mutant and parental strains grew at equivalent rates within human monocytes either in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 24 publications
5
96
2
Order By: Relevance
“…In a recent study, a ⌬dosR mutant of MTB was reported to be hypervirulent in both severe combined immunodeficient and DBA mice (29). In contrast, another recent report indicated that a ⌬dosR mutant of MTB was attenuated for virulence in guinea pigs (30). Thus, although both studies implicate the An electrophoretic mobility shift assay was performed using purified DosR or DosR (D54E) and a DNA probe containing a DosR binding motif in the presence or absence of the phosphate donor acetyl phosphate (Acetyl-P).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, a ⌬dosR mutant of MTB was reported to be hypervirulent in both severe combined immunodeficient and DBA mice (29). In contrast, another recent report indicated that a ⌬dosR mutant of MTB was attenuated for virulence in guinea pigs (30). Thus, although both studies implicate the An electrophoretic mobility shift assay was performed using purified DosR or DosR (D54E) and a DNA probe containing a DosR binding motif in the presence or absence of the phosphate donor acetyl phosphate (Acetyl-P).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mtb responses to NO and hypoxia were shown to be mediated by DosR/S/T and each induced the same transcription profiles (3)(4)(5). Also, Mtb dosR was shown to be essential for full virulence in guinea pigs (23), and iNOS knockout mice were demonstrated to be susceptible to Mtb infection (6). Finally, human Mtbinfected lungs were shown to produce active iNOS (7).…”
Section: Discussionmentioning
confidence: 99%
“…10,11,17 There is an inherent difficulty in using a coupled assay in a filter-based format owing to an inability to discriminate between the phosphorylated species of the histidine kinase and response regulator. Inhibitors of 2-component systems that inhibited the activity of AlgR1 and AlgR2 proteins regulating alginate biosynthesis in Pseudomonas aeruginosa were discovered using an algD-xylE reporter assay.…”
Section: Discussionmentioning
confidence: 99%
“…17 However, a devR knockout strain was reported by another laboratory to be hypervirulent in mice. 18 The contradictory findings in the mouse infection model 18 could be due to inherent differences in the 2 mutant strains, in the experimental models and the route of infection used (discussed in Malhotra et al 17 ). For these reasons, DevR is considered to be a crucial regulator of the dormancy response of M. tuberculosis.…”
mentioning
confidence: 99%